Influence of Shade in Cocoa Agroforestry Systems on Physicochemical and Functional Characteristics of Cocoa Beans in Bonon, Central-West Côte d’Ivoire - Affoué Tatiana Kouassi; Adjoua Christiane Eunice Boko; Sika Hortense Blei; Djédoux Maxime Angaman; Yao Sadaiou Sabas Barima (International Journal of Food Science)
Côte d’Ivoire remains the world’s leading producer of cocoa beans. However, cocoa farming is now recognized as a primary cause of deforestation in the country. To combat deforestation, the Ivorian government recently advocates for agroforestry, a farming technique involving the cultivation of cocoa trees with fruit or forest trees. Yet, the impact of these associated trees and their shade on the quality of produced cocoa beans remains relatively unknown. This study is aimed at evaluating the influence of tree shade in cocoa farms on the quality of cocoa beans produced in the Bonon area. Morphological, biochemical, and functional analyses were performed on cocoa beans from shaded, partially shaded, and sunny subplots. Overall, only beans from shaded subplots showed better commercial quality. Regarding nutritional potential, results demonstrated that acidity, protein content, and vitamin C levels were influenced by shade. Low protein levels were observed in beans from sunny areas. The presence of moderate shade significantly favored good foaming power and foam stability. These findings play a key role in the perceived quality and application of these beans in the food and cosmetic industry. Moreover, these discoveries open new research perspectives in the field of food biochemistry and sustainable agriculture.